2013
DOI: 10.1177/1359105313509846
|View full text |Cite
|
Sign up to set email alerts
|

The association of personal resilience with stress, coping, and diabetes outcomes in adolescents with type 1 diabetes: Variable- and person-focused approaches

Abstract: This study explored the association between personal resilience and distress, coping, and diabetes outcomes in 50 adolescents with type 1 diabetes. Resilience was defined by a factor score derived from validated instruments measuring self-efficacy, optimism, and self-esteem. Variable- and person-focused methodologies were used to explore these associations. Low resilience was associated with higher distress, poor quality of life, and poor glycemic control. Participants with low resilience used more maladaptive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
83
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(93 citation statements)
references
References 66 publications
7
83
0
3
Order By: Relevance
“…The cognitive adaptation index predicted lower levels of bulimic symptoms, lower levels of friend conflict, lower rates of romantic relationship breakup, and lower levels of alcohol use only for those with type 1 diabetes. These findings are consistent with a recent study of adolescents with type 1 diabetes that linked similar cognitive adaptation indicators to less distress, higher quality of life, and better glycemic control (45). Interestingly, the instances in which the cognitive adaptation index interacted with group and revealed links to benefits for those with diabetes only appeared at the Time 3 assessment.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The cognitive adaptation index predicted lower levels of bulimic symptoms, lower levels of friend conflict, lower rates of romantic relationship breakup, and lower levels of alcohol use only for those with type 1 diabetes. These findings are consistent with a recent study of adolescents with type 1 diabetes that linked similar cognitive adaptation indicators to less distress, higher quality of life, and better glycemic control (45). Interestingly, the instances in which the cognitive adaptation index interacted with group and revealed links to benefits for those with diabetes only appeared at the Time 3 assessment.…”
Section: Discussionsupporting
confidence: 92%
“…That is, their beliefs about personal control in the context of high self-esteem and an optimistic outlook might lead to increased persistence and a promotion-focused mentality. Research in the area of diabetes has show that resilience, operationalized in a way parallel to our cognitive adaptation index (i.e.,defined by self-esteem, optimism, and self-efficacy), was related to lower levels of maladaptive coping (e.g., withdrawal, self-criticism, denial, disengagment) and higher levels of adaptive coping (e.g., cognitive restructuring, problem solving, acceptance) in adolescents (45) and adults (58). In terms of our relationship outcomes, persons who are characterized by CAT indicators are likely to be viewed as more attractive to others.…”
Section: Discussionmentioning
confidence: 98%
“…46,16,31,32,37,38 Indeed, patient-reported outcomes have been encouraged in psychosocial oncology research because they allow better understanding of patients’ values, thereby informing clinical decision-making and providing patient-centered care. 39,40 While few studies explicitly describe patient-reported resilience amongst patients with cancer, 5,29,32,41 our data are consistent with others’ which suggest that personal perceptions of resilience play important roles in health and psychosocial outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Resilience, sometimes defined as the combination of self‐efficacy, optimism and self‐esteem but also intact social, emotional and behavioural functioning, is linked to lower distress levels and high quality of life . Resilience has also been found to moderate the association between childhood neglect and later psychiatric symptoms .…”
Section: Protective Factorsmentioning
confidence: 99%